Penggunaan Media Pembelajaran Wordwall Untuk Menumbuhkan Motivasi Belajar Peserta Didik Pada Mata Pelajaran Matematika: The Use of Wordwall Learning Media to Foster Students' Learning Motivation in Mathematics Subjects - Aswinarti Eka Putri, Tri; Djam’an, Nurwati; Rahim, Irmayana (Jurusan Pendidikan Teknik Elektro, 2025)
Learning motivation is the drive or enthusiasm that drives someone to actively seek, understand, and master new knowledge or skills. One thing that can foster learning motivation is the right learning media. This study aims to provide a description of the use of wordwalls in mathematics learning to foster learning motivation of class XI Electrical Power Installation Engineering students at SMK Negeri 3 Makassar. This research was conducted in class XI Electrical Power Installation Engineering at SMK Negeri 3 Makassar. The method used in this study is a qualitative research method with observation techniques carried out by collecting various information from direct observations in class XI TITL SMK Negeri 3 Makassar. The results of the study show that utilizing wordwalls in mathematics learning can foster student learning motivation. This makes students enthusiastic so that teachers can utilize wordwalls to support active student learning to achieve learning objectives using the independent curriculum.